Ethos present in teaching biological sciences: Brazilian research between 2017-2024 (Revista Contexto & Educação, 2026)
Research on Ethos — the culture, customs, and identities of a community — related to the teaching of Biological Sciences has been widely studied. This work is a systematic literature review aimed at answering the following question: what do the research studies published between 2017-2024, after the National Common Curricular Base, say about the teaching of Biological Sciences, from a longitudinal perspective of basic and higher education, in the cultural aspect and popular/ethnic knowledge? As a result, we found 48 studies, with the Southeast (13) and Northeast (13) regions having the largest productions, with a predominance of the locus of labor production in Basic Education (31). The predominant approach was qualitative, with a preponderance of research linked to cultural/popular knowledge in the themes of ethnobotany and environmental issues, in basic education, which demonstrates the lack of analysis of cultural knowledge when linked to Biological Sciences with other objects, in terms of national exams and curricular matrices, linked to knowledge diverse to Ethos. We conclude that popular/ethnic knowledge, such as the so-called ethnoknowledge/ethnoknowledge, are important cultural expressions, both of space-time and man-nature relations and can be used in the teaching of Biological Sciences at their different levels and that the curricula, despite being distinct, are at the same time universal, since several studies indicate that the specificities and needs of the context of each educational system are, at times, disregarded.
Keywords: Ethnoknowledge; Education; Culture